2018
DOI: 10.5109/2174855
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Green Paradox: Case Study of Japan

Abstract: Introducing renewable energy is progressing rapidly in various countries. It has long been thought that the introducing is not only extending the availability period of fossil fuels but also not directly discharging harmful substances into the atmosphere. In recent years, a concept of "Green Paradox" casts doubt on that ideas. According to the concept, the renewable energy introducing accelerates fossil fuels consumption and promotes the increase of harmful substances due to the consumption. Because the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…In addition, some Japanese industries say that raising the electricity price can be considered as a cause of overseas relocation. Therefore, these are phenomena are matching to the green paradox 16) . As to reduce the emissions of CO2, Developing 1D models for CO2 adsorption using different capture materials using CFD commercial software that has a built-in feature that can describe the multiscale mass transfer in the macro-and micro-pores 17) .…”
Section: Introductionmentioning
confidence: 86%
“…In addition, some Japanese industries say that raising the electricity price can be considered as a cause of overseas relocation. Therefore, these are phenomena are matching to the green paradox 16) . As to reduce the emissions of CO2, Developing 1D models for CO2 adsorption using different capture materials using CFD commercial software that has a built-in feature that can describe the multiscale mass transfer in the macro-and micro-pores 17) .…”
Section: Introductionmentioning
confidence: 86%
“…Actually similar difficulties to take countermeasures against environmental issues existed in currently developed societies as Sato et al, 2016 18) reported cases of Kitakyushu, Japan and Emscher, Germany during middle of 20 th century (Fujisaki, 2018) 19) . Nevertheless, developed countries already have strict regulations and implemented advanced technologies to control their local environmental issues as well as global environmental issues, in contrast, developing countries are struggling with lack of technology and economic development (United Nations, 2019) 20) .…”
Section: Introductionmentioning
confidence: 94%
“…Although the game theory as well as evolutionary game theory are well accepted, many works have been wheeled around its theoretical aspect or taking simulation approaches to solve down-to-earth questions; for instance, why cooperative behavior has been evolutionally favored in many animal species from human being to nature 6) . The experimental works vis-à-vis theory and simulation have been extensively studied, many pioneers have tried to validate the game theory by intrigued experimental efforts.…”
Section: Introductionmentioning
confidence: 99%